Between-day reliability of cytokines and adipokines for application in research and practice - Rose, Grace L.; Farley, Morgan J.; Flemming, Nicole B.; Skinner, Tina L.; Schaumberg, Mia A. (Frontiers in Physiology, 2022)
Purpose: This study assessed the biological reliability of peripheral human cytokines and adipokines, and the influence of participant characteristics on total error. This has essential application to interventional cytokine measurement to ensure that reported results are interpreted with confidence. Methods: Participants (49% female, 18-85 years, n=84) completed two consecutive-day testing sessions. Participants provided a venous blood sample at the same time of day across two consecutive days, under standardized participant presentation, including 24-hour rested and 12-hour fasted conditions. Multiplex immunoassay was used to assess inflammatory analytes from samples (predominantly plasma). Repeat measurements were conducted between-day for total precision quantification, and technical (technique) error was negated from the total to provide an estimate of biological (attributed to participant presentation) error. Results: Whilst there was no evidence of statistically significant biological error, a small amount of biological error was consistently present across most analytes (~3.3%/0.07 pg/mL), which was largest for measurement of leptin (7.3%/210 pg/mL). There was also an influence of sex on reliability of leptin and adiponectin (total model explained 6-7% of error variation), where females demonstrated the greatest error. Conclusion: Biological error reported in this study should be applied to any future study or individual with a repeated measurement of cytokine concentrations over time that maintain best practice procedures (12-hour fasted, 24-hour rested). In most cases, raw error should be used, with exceptions for women for measurement of leptin and adiponectin. This approach will ensure that results are reported with certainty for improved reporting of intervention efficacy.